E-engineering drawing (EED) - a web based system for teaching and learning engineering drawing for upper secondary schools - Shariffudin, Rio Sumarni; Lee, Ming Foong; Othman, Widad (2006)
Engineering drawing is a combination of geometrical and building, mechanical and electrical drawing. It relates between theory and picture of reality. Engineering drawing will provide an accurate and complete picture for every object in terms of shape and size. Individuals involved in the world of engineering must be able to read and interpret an engineering drawing. This is an important pre-requisite. Many researches showed that those who learn Engineering drawing encounter difficulties to see an image in 3dimension, in other words, visualisation. In Engineering drawing, information and specifications from the real object must be transferred to a drawing; likewise, interpretation of information from a drawing to produce a real image. The transfer from reality to a drawing and vice versa is not an easy task. Thus, a web-based system for teaching and learning Engineering drawing was developed based on the Visualisation and Constructivist Model. EEO™ is tailored for several topics of engineering drawing such as Orthographic Projection; Sectional View; Isometric and Oblique drawing at the secondary level. The learning strategy consists of multiple phases beginning with orientation, elicitation of ideas, reconstruction, application of concept and reflection. For example, in the orientation phase, students will be exposed to an overview of the topic followed by learning of specific concepts. Other phase involved eliciting of ideas reconstruction of concept and application of knowledge. This system also provides a learning environment that allows learners to view objects from different angles; such as third angle projection and first angle projection as well as views of plans, side and front elevations. The learners will be gUided through the various steps in drawing methods for each topic via animations and simulations. Learners are able to view any section repeatedly. Examples of real application of engineering drawings WIJl be also given using graphic, animations and video. To evaluate students understanding, exercises will be given at the end of each session. The effectiveness of the system will also be evaluated using students' interactive patterns while working at the interface.